Uncovering the Formula of Classical Javanese Literary Works: Structural Analysis of Power, Religion, and Subaltern Resistance - Nursalim, Misbah Priagung (Al-Adabiya: Jurnal Kebudayaan dan Keagamaan, 2025)
Classical Javanese literature is traditionally defined by its profound synonymy with religious authority and the royal court (power), a duality long observed but structurally underexplained. This research utilizes a qualitative descriptive method, synthesizing existing studies of canonical texts—including Negarakertagama, Pararaton, Arjuna Wiwaha, and Sutasoma—to reveal the tripartite sociological formula determining literary inception. The analysis establishes that classical literature was overwhelmingly produced by eloquent individuals monopolizing broad knowledge, typically religious leaders, kings, and royal scribes. This structural control resulted from three interlocking factors: 1) Caste, wherein literacy and intellectual production were restricted primarily to Brahmins and Kshatriyas; 2) Knowledge, disseminated through the elite Kadewaguruan education system, which prioritized religious ethics before statecraft, functioning as an ideological apparatus to generate loyal state officials and authorized literary works; and 3) Culture, which utilized mythical elements (Smita) to glorify kings as divine incarnations, thereby legitimizing political narratives. The overarching function of this literature was to perpetuate power and spread sanctioned religious doctrine. While groups outside the palace provided resistance, notably through accessible oral literature and written counter-narratives like Serat Gatoloco, this opposition often failed to fundamentally displace the dominant hegemony. Drawing on Gayatri Spivak’s postcolonial perspective, the findings demonstrate that while resistance existed, the systemic control over authorship, knowledge, and dissemination ensured the literary output remained fundamentally focused on centralized religious and political control. This research clarifies that the enduring characteristics of Javanese classical texts are directly rooted in the political and educational policies of the past.